2017
DOI: 10.1111/acer.13546
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Etheno DNA Adducts in Alcoholic Liver Disease: Correlation with Cytochrome P‐4502E1 and Fibrosis

Abstract: These data suggest an important role of CYP2E1 in the generation of εdA, in the fibrotic progression of ALD, and thus in alcohol-mediated hepatocarcinogenesis. CYP2E1 may be a target in the treatment of ALD and a potential prognostic marker for disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 49 publications
1
23
0
2
Order By: Relevance
“…The pathological role of CYP2E1 has been suggested elsewhere: for example, the deletion of the CYP2E1 gene decreased the development of alcoholic steatohepatitis, non‐alcoholic steatohepatitis, fast food‐mediated hepatofibrosis, and hepatocarcinogenesis, and there is a significant correlation between CYP2E1 determined by immunohistochemically and the stage of hepatofibrosis . Our present study found that higher CYP2E1 activity is a risk factor for hepatocarcinogenesis from hepatofibrosis, which was explained by metabolic activation of DEN.…”
Section: Discussionsupporting
confidence: 74%
“…The pathological role of CYP2E1 has been suggested elsewhere: for example, the deletion of the CYP2E1 gene decreased the development of alcoholic steatohepatitis, non‐alcoholic steatohepatitis, fast food‐mediated hepatofibrosis, and hepatocarcinogenesis, and there is a significant correlation between CYP2E1 determined by immunohistochemically and the stage of hepatofibrosis . Our present study found that higher CYP2E1 activity is a risk factor for hepatocarcinogenesis from hepatofibrosis, which was explained by metabolic activation of DEN.…”
Section: Discussionsupporting
confidence: 74%
“…Can be used as cancer markers [199]. They are carcinogenic and play an important role in initiating the process of hepatocarcinogenesis [200].…”
mentioning
confidence: 99%
“…), which may interfere with CYP expression and hepatic drug metabolism. Supporting this, the Heidelberg workgroup found reduced CYP2E1 expression in liver fibrosis, identified with liver stiffness elastography, as well as boosted CYP expression, drug metabolism, and subsequently increased, carcinogenic etheno-DNA adducts in (nonfibrotic) alcoholic liver disease [41, 42]. Therefore, the in-depth evaluation of CYP regulation in liver disease states is also of chief clinical relevance.…”
Section: Discussionmentioning
confidence: 99%